A Review Study On The Concept Of Dhumapana: A Procedure Of Dincharya - Kaur, Harjeet; Rani, Seema (International Research Journal of Ayurveda & Yoga, 2021)
Dhumapana is a medicated smoke inhalation procedure of dincharya regimen mentioned in Ayurveda text. Dhumapana is a procedure which is used as a preventive measure as well as promotive and curative method. It prevents vitiated vata and Kapha generated Urdhva jatrugata vyadhi (heaviness of head, headache, rhinitis, pain in eyes, ear, cough etc.). Vitiated kapha situated in the head is eliminated very fast by dhumapana. So, after application of collyrium smoking is prescribed. Inhalation of dhuma (smoke) from the dhumavarti(medicated cigar) which is made up of using different herbal drugs by placing it in dhumanetra, an instrument used for smoking. Dhumpana works as both shamana and shodhana therapy for vitiated dosha. The detailed description about the concept of dhumpana as mentioned in Ayurveda is elaborated in this article.